Collaborative health systems ECHO: The use of a tele-education platform to facilitate communication and collaboration with recipients of state targeted response funds in Pennsylvania. Issue 1 (1st December 2022) - Kawasaki, S.; Hwang, G.; Buckner, K.; Francis, E.; Huffnagle, S.; Kraschnewski, J.; Vulgamore, P.; Lucas, A.; Barbour, J.; Crawford, M.; Thomas, L.; Fuller, M.; et al.
Abstract: Background: The opioid epidemic continues to erode communities across Pennsylvania (PA). Federal and PA state programs developed grants to establish Hub and Spoke programs for the expansion of medications for opioid use disorders (MOUD). Employing the telementoring platform Project ECHO (Extension for Community Health Outcomes), Penn State Health engaged the other seven grant awardees in a Collaborative Health Systems (CHS) ECHO. We conducted key informant interviews to better understand impact of the CHS ECHO on health systems collaboration and opioid crisis efforts. Methods: For eight one-hour sessions, each awardee presented their unique strategies, challenges, and opportunities. Using REDCap, program characteristics, such as number of waivered prescribers and number of patients served were collected at baseline. After completion of the sessions, key informant interviews were conducted to assess the impact of CHS ECHO on awardee's programs. Results: Analysis of key informant interviews revealed important themes to address opioid crisis efforts, including the need for strategic and proactive program reevaluation and the convenience of collaborative peer learning networks. Participants expressed benefits of the CHS ECHO including allowing space for discussion of challenges and best practices and facilitating conversation on collaborative targeted advocacy and systems-level improvements. Participants further reported bolstered motivation and confidence. Conclusions: Utilizing Project ECHO provided a bidirectional platform of learning and support that created important connections between institutions working to combat the opioid epidemic. CHS ECHO was a unique opportunity for productive and convenient peer learning across external partners. Open dialogue developed during CHS ECHO can continue to direct systems-levels improvements that benefit individual and population outcomes.